The Analysis of Customer Satisfaction and Loyalty at Wong Solo Restaurant During the Covid-19 Pandemic in Kendari City - Isnar Sari; R. Marsuki Iswandi; Muhammad Aswar Limi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
This study analyzes customer satisfaction and loyalty at the Wong Solo restaurant during the Covid-19 pandemic in Kendari City. The type of data used in this research is primary data obtained through interviews with customers of the Wong Solo restaurant. This research was conducted in April 2022. The research location was determined purposively, and the number of samples in this study was 50 people—sampling using the Accidental Sampling method by specifying several criteria. The customer satisfaction index (CSI) and Brand Loyalty analysis are used. The results of this study indicate that the CSI value obtained, which is 70%, is in the satisfied category. Meanwhile, customer loyalty shows that customers are loyal to the performance and services the Wong Solo restaurant provides.